Steven Levistsky & Mauricio Zavaleta, ¿Por qué no hay partidos políticos en el Perú? Editorial Planeta Perú S. A. 2019, 82 pp. - Munaris Parco, Sonia Beatriz (2019)
Under the announcement of Peru Brief of the Editorial Planeta, present the seductive work of Steven Levistsky and Mauricio Zavaleta in a scene of political turmoil in Peru and South America, where the rulers do not enjoy sympathy of the population due to lack of ideological sustainability that should Have every political party.